2022
DOI: 10.1177/21925682221131540
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Pandemic on Spine Surgeons Worldwide: A One Year Prospective Comparative Study

Abstract: Study Design Survey Objective In March of 2020, an original study by Louie et al investigated the impact of COVID-19 on 902 spine surgeons internationally. Since then, due to varying government responses and public health initiatives to the pandemic, individual countries and regions of the world have been affected differently. Therefore, this follow-up study aimed to assess how the COVID-19 impact on spine surgeons has changed 1 year later. Methods A repeat, multi-dimensional, 90-item survey written in English… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The influence of COVID-19 on spine surgery in specific regions has also been reported [ 22 , 23 ]. Moreover, Louie et al conducted the first international study to assess the effects of COVID-19 among spine surgeons [ 24 ], and a follow-up study by Barajas et al showed the responses of spine surgeons throughout one year [ 25 ]. A scoring system for the triage of spine surgeries due to the limited medical and human resources was also suggested by two individual studies [ 18 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The influence of COVID-19 on spine surgery in specific regions has also been reported [ 22 , 23 ]. Moreover, Louie et al conducted the first international study to assess the effects of COVID-19 among spine surgeons [ 24 ], and a follow-up study by Barajas et al showed the responses of spine surgeons throughout one year [ 25 ]. A scoring system for the triage of spine surgeries due to the limited medical and human resources was also suggested by two individual studies [ 18 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite of these limitations, our interpretations can contribute on solving public health problems on emerging issues and health inequality on the COVID-19 pandemic. [25,26]…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Despite of these limitations, our global interpretations have met our objective by supporting international and rapid evidence to solve global emerging issues and economic inequality related to the COVID-19. [23,24]…”
Section: Strengths and Limitationsmentioning
confidence: 99%